2004
DOI: 10.1007/s00436-003-1007-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an experimental fasciolicide against immature and mature Fasciola hepatica in artificially infected calves

Abstract: The efficacy of 5-chloro-2-methylthio-6-(1-naphthyloxy)- 1H-benzimidazole, called "alpha", was tested against Fasciola hepatica. Fluke-free calves ( n=32) were divided into 8 groups and infected with 150 metacercariae per animal. All animals subsequently received a second infection with another 150 metacercariae, given at different time intervals aimed to produce flukes of differing ages within the experimental animals. When the flukes reached the required age in the animals, four groups were treated with a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…SO is capable of exerting an effect on the juvenile TCBZresistant F. hepatica. It is uncertain whether this is significant enough to yield an efficacy similar to those reported against a presumably TCBZ-susceptible Mexican isolate (Hernández-Campos et al 2002;Ibarra et al 2004;Vera Montenegro et al 2004). An in vivo study involving Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…SO is capable of exerting an effect on the juvenile TCBZresistant F. hepatica. It is uncertain whether this is significant enough to yield an efficacy similar to those reported against a presumably TCBZ-susceptible Mexican isolate (Hernández-Campos et al 2002;Ibarra et al 2004;Vera Montenegro et al 2004). An in vivo study involving Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In in vivo treatments involving sheep, the activity against all stages of the parasite was found to be between 86.9 and 100% using a dose of 15 mg/kg (Ibarra et al 1997a(Ibarra et al ,b, 1999Rivera et al 2002). With infected cattle, compound alpha (at 12 mg/kg) displayed an efficacy of 98.1-100% against all stages of the fluke (Vera Montenegro et al 2003Montenegro et al , 2004). An in vitro study using the Sligo TCBZresistant isolate showed that compound alpha is capable of disrupting the tegument and associated tegumental cells of mature flukes following 24 h of incubation with the sulphoxide metabolite of compound alpha (McConville et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In order to maintain control of fascioliasis, it is necessary to develop new drugs or make-do with existing drugs. With regard to new drugs, a derivative of TCBZ known as compound alpha has been developed (Hernández-Campos et al 2002;Vera Montenegro et al 2004;McConville et al 2008). Much interest has been shown in artemisinin-type compounds, which have been used as antimalarials and are active against schistosomes (Caffrey 2007;Keiser and Utzinger 2007a;Utzinger et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Considering the fasciolicidal efficacy previously shown by the compound 5-chloro-2-(methylthio)-6-(1-naphthyloxy)-1H-benzimidazole, known as compound alpha , in sheep and cattle, (Ibarra et al 1997(Ibarra et al , 2000Vera et al 2001Vera et al , 2003Vera et al , 2004Rivera et al 2002Rivera et al , 2004Rivera et al , 2005, it was deemed relevant to modify its chemical structure and synthesize alpha-carbamate aimed at testing this new compound at the intestinal level against paramphistomids in sheep.…”
Section: Introductionmentioning
confidence: 99%